2007
DOI: 10.1177/1356336x07072678
|View full text |Cite
|
Sign up to set email alerts
|

Developmental coordination disorder and reported enjoyment of physical education in children

Abstract: Children with developmental coordination disorder (DCD) are less likely to enjoy participating in physical education (PE) than children without motor coordination difficulties. However, no studies have attempted to quantify this relationship or examine potentially modifiable mediating variables. Using a large sample ( N = 590) of children (aged 9 to 14), we examine differences in the enjoyment of PE classes between children with DCD and those without using a standardized measure. We also examine whether differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
0
18

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 32 publications
2
43
0
18
Order By: Relevance
“…Considering the data pointed by the literature, the estimated prevalence of DCD is 5 to 15% of school-age children (5-11 years) (APA, 2002;Cairney, Hay, Mandigo, Wade, Faught, & Flouris, 2007;França, 2008;Miranda, Beltrame, & DCD prevalence in São Carlos -SP | 25 Cardoso, 2011;Silva, Contreira, Beltrame, & Sperandio, 2011 In this sense, it was necessary to calculate the sample size to detect an expected prevalence of 10% with 90% confidence and a maximum error of 5%. To ensure the validity of the study a minimum sample of 97 individuals would be required.…”
Section: Samplementioning
confidence: 99%
See 1 more Smart Citation
“…Considering the data pointed by the literature, the estimated prevalence of DCD is 5 to 15% of school-age children (5-11 years) (APA, 2002;Cairney, Hay, Mandigo, Wade, Faught, & Flouris, 2007;França, 2008;Miranda, Beltrame, & DCD prevalence in São Carlos -SP | 25 Cardoso, 2011;Silva, Contreira, Beltrame, & Sperandio, 2011 In this sense, it was necessary to calculate the sample size to detect an expected prevalence of 10% with 90% confidence and a maximum error of 5%. To ensure the validity of the study a minimum sample of 97 individuals would be required.…”
Section: Samplementioning
confidence: 99%
“…There are three cutoff points for DCD identification, and the age group of 5 to 7 years and 11 months, the score of 1-46 indicates that the child is suspected of having DCD; 8 to 9 years and 11 months, a score of 1-55 identifies that children have DCD signals; 10 to 14 years and 11 months, children between 1-57 scores are suspected of having DCD. The cutoff score used was validated in Canada (Cairney et al, 2007;Prado, Magalhães, & Wilson, 2009;Wilson, Kaplan, Crawford, & Roberts, 2007).…”
Section: Instrumentsmentioning
confidence: 99%
“…Recently, a number of studies have shown that children with DCD show poor performance in health-related physical fitness components. In particular, their physical fitness performance is substantially lower than that of their typically developing (TD) counterparts in the components explosive power, muscle strength and endurance [3][4][5][6][7] , and cardiorespiratory fitness 4,6,[8][9][10] . However, performance differences in physical fitness components between children with DCD and TD children were not confirmed in a sample with very young children at four to six years of age 6 , and the distinction is still ambiguous for the flexibility component 11 .…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that children with gross motor problems are less likely to participate in games and play requiring skills like jumping, running, or throwing balls and that they tend to be physically less fit than typically developing children (Cairney et al, 2005b;Cairney et al, 2007;Emck, Bosscher, van Wieringen, Beek, & Doreleijers, 2011;Hands & Larkin, 2006). Moreover, gross motor problems are associated with negative selfperceptions (Peens, Pienaar, & Nienaber, 2008;Piek, Baynam, & Barrett, 2006;Poulsen, Ziviani, & Cuskelly, 2006;Skinner & Piek, 2001).…”
mentioning
confidence: 99%